Niveles de transaminasas en pobladores adultos de ambos sexos que acuden al centro poblado de Santa Elena de la provincia de Virú, departamento La Libertad, noviembre-2011” - Blas Narváez, Elizabeth Pilar (2012)
In this study we determined serum levels of transaminases (glutamic oxaloacetic transaminase and glutamic pyruvic transaminase) in adults of both sexes people who come to the town of Santa Elena center of the province of Viru, Department of Freedom, November-2011, working with volunteers who attended the St. Helena health Center in the span of 8:30 to 11:00 a.m., on 01 and 02 December, informing them of the methodology to conduct a personal interview and signed an informed consent by applying a survey to better interpret the results. Finally we went to the extraction of the blood sample, the same as after a centrifugation and collection of serum, was taken to the laboratory of Biochemistry, Faculty of Pharmacy and Biochemistry, where he proceeded to the determination of transaminase by the colorimetric method, 90 being obtained as sample size determinations of which due to the exclusion criteria was obtained 83 determinations for GOT was elevated in 2 people (2.4%), suspected none (0%) and normal (97.6%) and for GPT elevated in 6 people (7.2%), suspected none (0%) and normal in 77 people (92.8%). From which age with highest concentration of GOT was 42 to 53 years with 2 people and age with highest concentration of GPT was 42 to 53 years with 4 people, 1 person 18 to 29 years old and 1 person from 54 to 65 years of age with elevated transaminase levels. Of 65 women in a high concentration is GOT and GPT concentration 5, with respect to the 18 men in this high a concentration of GOT and GPT 1 concentration